2011
DOI: 10.1007/s00726-011-1066-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic RGD peptides interfere with binding of the Helicobacter pylori protein CagL to integrins αVβ3 and α5β1

Abstract: The human pathogen Helicobacter pylori that may cause different gastric diseases exploits integrins for infection of gastric cells. The H. pylori protein CagL present on the outer region of the type IV secretion pilus contains an RGD sequence (-Arg-Gly-Asp-) that enables binding to cells presenting integrins α5β1 and αVβ3. This interaction can be inhibited with conformationally designed cyclic RGD peptides derived from the CagL epitope -Ala-Leu-Arg-Gly-Asp-Leu-Ala-. The inhibition of the CagL-αVβ3 interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 55 publications
(58 reference statements)
3
58
0
Order By: Relevance
“…Further importance of CagL RGD-mediated integrin binding was reported using a cyclic RGD peptide, which 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 interferes with binding of Hp CagL to integrins, such as aVb3 [15].…”
Section: Introductionmentioning
confidence: 93%
“…Further importance of CagL RGD-mediated integrin binding was reported using a cyclic RGD peptide, which 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 interferes with binding of Hp CagL to integrins, such as aVb3 [15].…”
Section: Introductionmentioning
confidence: 93%
“…These data indicate that CagL undergoes significant conformational changes in solution in response to pH that are equivalent to those observed in the crystal structures. CagL Adherence to Host Cells and Functional Consequences Are pH-dependent-Numerous studies have shown that CagL binds to human gastric epithelial cells dependent on its RGD motif to cell surface integrins ␣ 5 ␤ 1 , ␣ V ␤ 5 , and ␣ V ␤ 3 and that this interaction is an essential step for the delivery of the effector protein CagA into host cells (8,19,20). RGD motifs are common to many proteins that bind integrins and, prior to the originally published CagL structure (23), were found exclusively in loop sequences.…”
Section: Cagl Stability Increases With Reduced Ph-translocation Ofmentioning
confidence: 99%
“…This interaction can be inhibited with conformational designed cyclic RGD peptides derived from the CagL epitope ALRGDLA (-Ala-Leu-ArgGly-Asp-Leu-Ala-). 92 Inhibition of the CagL-α v β 3 interaction by different RGD peptides verified the importance of the RGD motif for CagL binding capabilities. In agreement with these findings, CagL RAD and CagL RGA point mutants exhibited decreased affinity to integrin α v β 3 .…”
Section: Targeting Of Gp130 and Jak/stat Signaling By Injected Cagamentioning
confidence: 99%
“…In agreement with these findings, CagL RAD and CagL RGA point mutants exhibited decreased affinity to integrin α v β 3 . 92 Moreover, structureactivity relationship studies with cyclic RGD peptides in a spatial screening approach revealed a distinct influence of the threedimensional arrangement in the RGD motif on the ability to interfere with this interaction, however, an H. pylori-triggered downstream signaling cascade is yet unknown for integrin α v β 3 . Nevertheless, the above studies strongly suggest that H. pylori can target an array of at least three integrin members on epithelial cells for different purposes.…”
Section: Targeting Of Gp130 and Jak/stat Signaling By Injected Cagamentioning
confidence: 99%